Exploring fluoroquinolone resistance mechanisms and the effects of carbonyl cyanide 3-chlorophenylhydrazone (CCCP) in Acinetobacter baumannii - Nazari, Mohsen; Alikhani, Mohammad Sina; Hemmati, Jaber; Ahmadi, Amjad; Hashemi, Seyyed Hamid; Alikhani, Mohammad Yousef (Frontiers in Medicine, 2025)
ObjectivesThis study aims to investigate the prevalence and mechanisms of fluoroquinolone resistance in Acinetobacter baumannii strains isolated from hospitals in Hamadan, west of Iran. It investigates the role of specific resistance genes and mutations in contributing to this resistance. In addition, the effects of carbonyl cyanide 3-chlorophenylhydrazone (CCCP) on the susceptibility of A. baumannii to fluoroquinolones will be evaluated to identify potential strategies to combat this growing problem.MethodsA total of 102 A. baumannii isolates were collected from various clinical specimens between February and August 2023. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method according to CLSI guidelines, focusing on eight antibiotics, including ciprofloxacin and levofloxacin. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) evaluations were also performed for these fluoroquinolones. The presence of plasmid-dependent fluoroquinolone resistance (PMQR) genes and mutations in the gyrA and parC genes were assessed by PCR. The effect of CCCP on antibiotic susceptibility and expression of efflux pump encoding gene was evaluated by real-time PCR.ResultsThe study revealed alarmingly high resistance rates among the 102 A. baumannii isolates, with 97% resistant to imipenem, 96% to gentamicin, 92% to ciprofloxacin, and 86% to levofloxacin. Of the isolates, 87 were classified as multidrug resistant (MDR). Several resistance genes were identified, including qnrS (77.45%), oqxA (73.52%), and qnrA (72.54%). Mutations in the gyrA and parC genes were detected in several isolates, contributing to the observed resistance. In addition, treatment with CCCP resulted in a significant reduction in MICs for both ciprofloxacin and levofloxacin, highlighting its potential role in mitigating resistance.ConclusionThe findings underscore the urgent need for improved surveillance and treatment strategies due to the high prevalence of fluoroquinolone resistance. While CCCP demonstrated potential in restoring antibiotic susceptibility, further studies are needed to assess its clinical applicability and potential toxicity. Additionally, the study is limited by its focus on a single geographic region, and further investigations across broader populations are necessary to generalize these findings.